Sisters - Johnson, Daisy, 1990- (Riverhead Books, 2020)
"'One of her generation's most intriguing authors' (Entertainment Weekly), Daisy Johnson is the youngest writer to have been shortlisted for the Man Booker Prize. Now she returns with Sisters, a haunting story about two sisters caught in a powerful emotional web and wrestling to understand where one ends and the other begins. Born just ten months apart, July and September are thick as thieves, never needing anyone but each other. Now, following a case of school bullying, the teens have moved away with their single mother to a long-abandoned family home near the shore. In their new, isolated life, July finds that the deep bond she has always shared with September is shifting in ways she cannot entirely understand. A creeping sense of dread and unease descends inside the house. Meanwhile, outside, the sisters push boundaries of behavior -- until a series of shocking encounter tests the limits of their shared experience, and forces shocking revelations about the girls' past and future. Written with radically inventive language and imagery by an author whose work has been described as "entrancing" (The New Yorker), "a force of nature" (New York Times Book Review), and "weird and wild and wonderfully unsettling" (Celeste Ng), Sisters is a one-two punch of wild fury and heartache -- a taut, powerful, and deeply moving account of sibling love and what happens when two sisters must face each other's darkest impulses"--